Panoramic view of diversity and function of cuticular proteins in insects and mosquitoes biology - Thakur, Yamini; Tevatiya, Sanjay; Kumar, Gaurav; Jeena, Meenakshi; Verma, Vaishali; Dixit, Rajnikant; Pasi, Shweta; Eapen, Alex; Kaur, Jaspreet (Frontiers in Insect Science, 2025)
AimThe insect cuticle, vital for structural maintenance, forms their exoskeleton. It is mainly composed of an intermesh of – structural cuticle proteins (CPs) with polysaccharide chitin. The insect CPs encoded by CP genes are indispensable for morphology, development and adaptation to various ecological niches across all life stages. The number of CPs may vary across genera and species, with almost 150 proteins in Bombyx mori and more than 298 CPs found in Anopheles gambiae. While they have been extensively studied in insects such as agricultural pests, limited studies have been conducted on mosquitoes, particularly those relevant to public health, such as the Anopheles a key malaria vector.ObjectiveThis review recapitulates current knowledge on CPs in insects, while also underscoring vital knowledge gaps regarding regulation and metabolic crosstalk of CPs with other signaling and/or metabolic pathways.MethodsWe performed a comprehensive review of published studies and extracted data from databases including Vectorbase and NCBI with the aim of retrieving information on cuticular proteins, their gene families, abundance and associated functions. Additionally, we identified and analyzed the gaps in the available information. A literature search was conducted between (2000 and 2025) in an electronic database using PubMed, Scopus and Google Scholar. The search keywords were: cuticular proteins, cuticular genes, Anopheles, mosquito cuticle proteins, insecticide resistance, and CP gene families.Inclusion criteria: peer-reviewed research articles and review papers particularly focused on CPs in insects and Anopheles mosquito species.ResultsIn the present review, we provide comprehensive analysis of cuticle protein families across insects including mosquitoes based on available data. We further highlight their basic constituents and protein domain structure, offering insight into their role in insect physiology. We have effectively integrated insect studies with mosquito-specific research on CPs (bridging the gap between insect and mosquito-specific research). This holistic approach would facilitate a broader comprehension of CPs in both insect and mosquito vectors.Main conclusionsThe goal of this study is to enhance our understanding of insects and Anopheles biology and how studies on CPs could be leveraged to develop novel strategy for management of pest and combat vector-borne diseases (VBDs).